2024
DOI: 10.3390/biomedicines12020461
|View full text |Cite
|
Sign up to set email alerts
|

L-DOS47 Elevates Pancreatic Cancer Tumor pH and Enhances Response to Immunotherapy

Bruna Victorasso Jardim-Perassi,
Pietro Irrera,
Oluwaseyi E. Oluwatola
et al.

Abstract: Acidosis is an important immunosuppressive mechanism that leads to tumor growth. Therefore, we investigated the neutralization of tumor acidity to improve immunotherapy response. L-DOS47, a new targeted urease immunoconjugate designed to neutralize tumor acidity, has been well tolerated in phase I/IIa trials. L-DOS47 binds to CEACAM6, a cell-surface protein that is highly expressed in gastrointestinal cancers, allowing urease to cleave endogenous urea into two NH4+ and one CO2, thereby raising local pH. To tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This was experimented on a model of pancreatic tumors in mice, and it was observed that L-DOS47 elevated the extracellular pH of the tumor. When L-DOS47 was used in conjunction with anti-PD-1, it significantly boosted the effectiveness of the monotherapy, leading to a reduction in tumor growth for a duration of up to 4 weeks [ 482 ]. This study paves the way for using L-DOS47 in future clinical trials.…”
Section: Potential Strategies Improving Efficacy Of Pancreatic Cancer...mentioning
confidence: 99%
“…This was experimented on a model of pancreatic tumors in mice, and it was observed that L-DOS47 elevated the extracellular pH of the tumor. When L-DOS47 was used in conjunction with anti-PD-1, it significantly boosted the effectiveness of the monotherapy, leading to a reduction in tumor growth for a duration of up to 4 weeks [ 482 ]. This study paves the way for using L-DOS47 in future clinical trials.…”
Section: Potential Strategies Improving Efficacy Of Pancreatic Cancer...mentioning
confidence: 99%